A suggested vital function for eIF-5A and dhs genes during murine malaria blood-stage infection - Kersting, David; Sattler, Julia M.; Müller, Ann-Kristin (FEBS Open Bio, 2016)
The biological function of the post-translational modification hypusine in the eukaryotic initiation factor 5A (EIF-5A) in eukaryotes is still not understood. Hypusine is formed by two sequential enzymatic steps at a specific lysine residue in the precursor protein EIF-5A. One important biological function of EIF-5A which was recently identified is the translation of polyproline-rich mRNA, suggesting its biological relevance in a variety of biological processes. Hypusinated eIF-5A controls the proliferation of cancer cells and inflammatory processes in malaria. It was shown that pharmacological inhibition of the enzymes involved in this pathway, deoxyhypusine synthase (DHS) and the deoxyhypusine hydroxylase (DOHH), arrested the growth of malaria parasites. Down-regulation of both the malarial eIF-5A and dhs genes by in vitro and in vivo silencing led to decreased transcript levels and protein expression and, in turn, to low parasitemia, confirming a critical role of hypusination in eIF-5A for proliferation in Plasmodium. To further investigate whether eIF-5A and the activating enzyme DHS are essential for Plasmodium erythrocytic stages, targeted gene disruption was performed in the rodent malaria parasite Plasmodium berghei. Full disruption of both genes was not successful; instead parasites harboring the episome for eIF-5A and dhs genes were obtained, suggesting that these genes may perform vital functions during the pathogenic blood cell stage. Next, a knock-in strategy was pursued for both endogenous genes eIF-5A and dhs from P. berghei. The latter resulted in viable recombinant parasites, strengthening the observation that they might be essential for proliferation during asexual development of the malaria parasite.
Im Titel sind "eIF-5A" und "dhs" kursiv geschrieben
Gesehen am 21.11.2018